Legal assessment of Article (1) of Law No.21 of 2003 of the Iraqi Kurdistan Region. - Naska Ahmad Hawez; Mohammed Rashid Hasan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The crimes that are against the constitutional institutions vary and differ, they have many dimensions, it should be noted that these crimes can be political crimes and they can be ordinary crimes as they are committed through different behaviors and words, that these crimes affect the institutions of the region and harm them by nature, and they have Serious repercussions on the stability and security of the institutions of the Kurdistan Region of Iraq, and their dangers may lead to the location of the region and its constitutional entity. They are apparent crimes committed through criminal acts, which may cause material damage to the institutions of the region, and they have been organized within the framework of the laws of the region in the first law No. (21) of the year (2003), as it promises crimes against the internal security of the region and affects the stability and security of the region in general and the institutions in particular, we want to say that the Kurdistan legislator was not successful in enacting this law, because he used the concepts extensively and this contradicts the rights and freedoms of citizens, and its penalties are not Balanced and not appropriate for the multiple crimes committed, and we believe that the texts of the laws must be accurate and comprehensive, and their words and phrases are clear and understandable, so we believe that this law should re-legislate them,to include and regulate many other provisions and offences.